Promoting Student Performance in STEM EDP Model on Climate Change Topics - Vika Yulinda Antika; Nurul Fitriyah Sulaeman; Abdul Hakim (Vidya Karya, 2023)
Performance assessment is an authentic assessment that can be done with various kinds of assessments such as written assessments, observation, and assignments that can provide better feedback on performance and skills. Learning using STEM-EDP model is a learning that encourage students enggagement and in line with performance assessment. The topic in this lesson is climate change, that is relate with with global issue and suitable for STEM-EDP learning. The purpose of this study was to find out how the performance assesment category of class VII F students at Public Junior Highschool in Samarinda. This research uses a quantitative descriptive approach. The sample of this research was 31 students who were taken by cluster random sampling technique. The instruments used in this study were student worksheets and student performance rubrics. The results of the study obtained a process performance value of 78.3 and 78.6 which describes the process performance in the good category. The product performance values are 81.3 and 83.9 which fall into the very good category.The performance of students need to be promoted by more STEM EDP learning especially in junior high school level.